Bridges of Altantropa Workshop - Antoniou, Klitsa (My University, 2026)
Bridges of Altantropa Workshop, ECOLE FRANCO-Chypriote, Nicosia, Cyprus. Organized in the frame of Malta Pavilion at Venice Art Biennale. Sponsored by the Bank of Valletta and supported by the Malta Arts Council.